1997
DOI: 10.1183/09031936.97.10092040
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of antibodies to cytomegalovirus and other herpes viruses in pulmonary fibrosis

Abstract: The aim of this study was to determine whether latent viral infection is associated with idiopathic pulmonary fibrosis (IPF), an interstitial lung disease whose aetiology remains to be elucidated.Cytomegalovirus ( Increases in cytomegalovirus immunoglobulin G and complement fixation titres with negative cytomegalovirus immunoglobulin M suggest that latent cytomegalovirus infection may be more prominent in idiopathic pulmonary fibrosis or collagen vascular disease-related interstitial pneumonitis. Together with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 24 publications
(28 reference statements)
1
55
0
1
Order By: Relevance
“…Increased titers of antibodies to cytomegalovirus and Epstein Barr virus have been noted in IPF patients (89). Herpesvirus antigens can be detected in AECs lining areas of fibrosis in IPF lung biopsy samples but not in lung epithelium of controls (15,35,73).…”
Section: Potential Causes Of Er Stress In Ipfmentioning
confidence: 85%
“…Increased titers of antibodies to cytomegalovirus and Epstein Barr virus have been noted in IPF patients (89). Herpesvirus antigens can be detected in AECs lining areas of fibrosis in IPF lung biopsy samples but not in lung epithelium of controls (15,35,73).…”
Section: Potential Causes Of Er Stress In Ipfmentioning
confidence: 85%
“…Subsequently, there have been multiple reports of herpesvirus detection by serology or PCR with increased frequency in subjects with IPF (4,11,36). Using PCR, Tang et al (32) found that 97% of patients with IPF had herpesvirus DNA present in lung tissue [including EBV, cytomegalovirus (CMV), human herpesvirus 7, and/or human herpesvirus 8] compared with 36% of normal lungs.…”
Section: Human Studiesmentioning
confidence: 99%
“…Another line of evidence suggesting that pulmonary fibrosis is related to epithelial cell dysfunction is the correlation between certain latent viral infections, such as EBV, CMV, HHV-7, and HHV-8, and human IPF (17,18,35,42,77,85,90). Such viruses are known to infect and remain latent in pulmonary epithelial cells (75), thereby potentially rendering them less able to repair following subsequent injury.…”
Section: Defects In Alveolar Epithelial Cells Underlying Disease Pathmentioning
confidence: 99%